Pengaruh Pembiasaan Membaca Surah Yasin Sebelum Pembelajaran Terhadap Kecerdasan Spiritual Peserta Didik Kelas IX Di MTs Ribatul Muta’allimin Pekalongan - Nahdliyah, Nafakhatin; Nalim, Nalim (STAI YAPIS Takalar, 2025)
Character building for students is a crucial aspect of education, particularly in instilling moral and religious values. One approach is through habituation methods, such as reciting Surah Yasin before class. This habituation is expected to foster students' spiritual intelligence, especially during adolescence, when they are vulnerable to negative environmental influences. Spiritual intelligence plays a crucial role in equipping students to face life's challenges and distinguishing between good and bad behavior. This study aimed to determine the effect of reciting Surah Yasin before class on the spiritual intelligence of ninth-grade students at MTs Ribatul Muta'allimin Pekalongan. The study used a quantitative approach with simple linear regression. Data were collected through questionnaires distributed to ninth-grade students. The study population was 192 students, with a sample of 77 students drawn using cluster sampling. Data analysis was performed using t-tests, F-tests, and regression. The results showed that reciting Surah Yasin before class significantly impacted students' spiritual intelligence. The average score for the habitual reading of Surah Yasin was 82.59, while for spiritual intelligence, it was 86.67. The t-test and F-test results indicated a significant effect, supported by regression results showing that every one-point increase in habitual reading of Surah Yasin increased spiritual intelligence by 0.674 points. These findings confirm that the habitual reading of Surah Yasin before class is effective in supporting the development of students' spiritual character. Therefore, schools are advised to maintain and develop religious habitual activities by involving teachers and parents. Future research is expected to develop variables and research methods to obtain more comprehensive results